An Analysis of Rhetorical Moves and Steps of Findings and Discussions of “Cyberbullying in the Name of God: Critical Discourse Analysis of Online Responses to the Act of De-hijabbing in Malaysia” (Universitas Negeri Semarang, 2023)
This research is a kind of Discourse Analysis by using Moves and Steps proposed by Ruiying Allison (2003) to analyze a Research Article in the 3L Journal entitled “Cyberbullying in the Name of God: Critical Discourse Analysis of Online Responses to the Act of De-hijabbing in Malaysia“. The researchers used the Moves and Steps analysis model to analyze the Findings and Discussion section in that Research Article. Based on the research analysis, it can be found that the authors of the research article applied 7 of 7 Moves and only applied 5 of 10 Steps. Some of the Steps that were not implemented in the research article were M4/S3, M6/S2, M7/S1, M7/S2, and M7/S3.